The Influence of Entrepreneurial Interest and Social Media Utilization By Gen Z on MSME Goat Farming Marketing: A Study on Duo Saudara Goat Farm in Bojonegoro Regency - Nafisah, A’isy Fiklil; Sudarmiatin; Wardana, Ludi Wishnu (International Humanity Advance, Business & Sciences, 2024)
This study aims to analyze the influence of entrepreneurial interest and social media utilization by Generation Z on the marketing effectiveness of micro, small, and medium enterprises (MSMEs) in goat farming. The research was conducted on Duo Saudara Goat Farming MSME in Bojonegoro Regency using a quantitative approach. Data were collected through questionnaires distributed to 60 respondents, consisting of consumers and goat farm managers. Data analysis was performed using SPSS software to examine the relationship and impact between independent variables (entrepreneurial interest and social media utilization) and the dependent variable (MSME marketing). The results showed that both entrepreneurial interest and social media utilization significantly influence the marketing effectiveness of goat farming MSMEs. Social media utilization by Generation Z contributed more dominantly than entrepreneurial interest, particularly in reaching broader markets and enhancing consumer interaction. The implications of this study indicate the importance of improving digital competencies among MSME practitioners to maximize marketing potential. This study provides empirical contributions to the development of MSME marketing strategies by leveraging modern technology and the entrepreneurial interests of the younger generation.